Fully automated radiolabeling of [68Ga]Ga-EMP100 targeting c-MET for PET-CT clinical imaging - Timofei Rusu; Matthieu Delion; Charlotte Pirot; Amaury Blin; Anita Rodenas; Jean-Noël Talbot; Nicolas Veran; Christophe Portal; Françoise Montravers; Jacques Cadranel; Aurélie Prignon (SpringerOpen, 2023)
Abstract Background c-MET is a transmembrane receptor involved in many biological processes and contributes to cell proliferation and migration during cancer invasion process. Its expression is measured by immunehistochemistry on tissue biopsy in clinic, although this technique has its limitations. PET-CT could allow in vivo mapping of lesions expressing c-MET, providing whole-body detection. A number of radiopharmaceuticals are under development for this purpose but are not yet in routine clinical use. EMP100 is a cyclic oligopeptide bound to a DOTA chelator, with nanomolar affinity for c-MET. The aim of this project was to develop an automated method for radiolabelling the radiopharmaceutical [68Ga]Ga-EMP100. Results The main results showed an optimal pH range between 3.25 and 3.75 for the complexation reaction and a stabilisation of the temperature at 90 °C, resulting in an almost complete incorporation of gallium-68 after 10 min of heating. In these experiments, 90 µg of EMP-100 peptide were initially used and then lower amounts (30, 50, 75 µg) were explored to determine the minimum required for sufficient synthesis yield. Radiolysis impurities were identified by radio-HPLC and ascorbic acid and ethanol were used to improve the purity of the compound. Three batches of [68Ga]Ga-EMP100 were then prepared according to the optimised parameters and all met the established specifications. Finally, the stability of [68Ga]Ga-EMP100 was assessed at room temperature over 3 h with satisfactory results in terms of appearance, pH, radiochemical purity and sterility. Conclusions For the automated synthesis of [68Ga]Ga-EMP100, the parameters of pH, temperature, precursor peptide content and the use of adjuvants for impurity management were efficiently optimised, resulting in the production of three compliant and stable batches according to the principles of good manufacturing practice. [68Ga]Ga-EMP100 was successfully synthesised and is now available for clinical development in PET-CT imaging.